PENGARUH WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN ALAT TULIS KANTOR PADA UD. ZAM-ZAM DI BTP KOTA MAKASSAR - Saputri, Della Awalanda; Mahyus (Innovation For Quality Business Admin And Technology (INQUBATE), 2024)
Test and analyze the influence of Word of Mouth on Office Stationery Purchasing Decisions at UD. Zam-Zam at BTP Makassar City. Uses quantitative research which aims to determine the influence or relationship between two or more variables. This research uses simple linear regression data analysis techniques, t hypothesis testing and coefficient of determination tests to measure the hypothesis using statistical product and service solution (SPSS 16) software. The word of mouth variable or variable Zam-Zam at BTP Makassar City.